2009
DOI: 10.3322/caac.20028
|View full text |Cite
|
Sign up to set email alerts
|

Review of Preoperative Magnetic Resonance Imaging (MRI) in Breast Cancer: Should MRI Be Performed on All Women with Newly Diagnosed, Early Stage Breast Cancer?

Abstract: Randomized controlled trials have shown equivalent survival for women with early stage breast cancer who are treated with breast-conservation therapy (local excision and radiotherapy) or mastectomy. Decades of experience have demonstrated that breast-conservation therapy provides excellent local control based on defined standards of care. Magnetic resonance imaging (MRI) has been introduced in preoperative staging of the affected breast in women with newly diagnosed breast cancer because it detects additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
150
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(158 citation statements)
references
References 84 publications
2
150
0
6
Order By: Relevance
“…Although many studies have assessed the value of using magnetic resonance imaging (MRI) in invasive breast cancer, its role in clinical practice is still disputed. Some studies have suggested that MRI may increase rates of mastectomies, probably by overestimating the extent of local disease (1,2). In many of these studies, short-term clinical outcomes were the primary endpoints.…”
mentioning
confidence: 99%
“…Although many studies have assessed the value of using magnetic resonance imaging (MRI) in invasive breast cancer, its role in clinical practice is still disputed. Some studies have suggested that MRI may increase rates of mastectomies, probably by overestimating the extent of local disease (1,2). In many of these studies, short-term clinical outcomes were the primary endpoints.…”
mentioning
confidence: 99%
“…Several review articles published by Houssami et al [11][12][13] strongly maintained that breast MRI would only cause more patients suitable for BCT to undergo more radical surgery without evidence to indicate improved survival. However, missed multicentric disease may be responsible for future recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews by Houssami et al [11][12][13] argued that consistently, MRIs changed surgical management, usually from breast conservation to more radical surgery, but there was no evidence of associated improved surgical outcomes or prognosis. More importantly, the recent randomised COMICE trial 14 concluded that MRI might be unnecessary as a means of reducing reoperation rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is not known whether additional tumors detected on MRI could be treated exclusively with adjuvant radiotherapy [31][32][33]35 . So, several studies reported a rate of change of surgical plan to mastectomy or to wider resections between 8.3 and 43% 18,19,23,24,28,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The rates of multifocality, multicentricity and contralateral breast lesions in the 60 patients of our series were 26.7, 1.7 and 8.3% respectively. Houssami and Hayes, in a series with 2,610 patients, detected 40% of multifocal and multicentric tumors 31 . COMICE trial detected 16% of multifocal tumors 13 .…”
Section: Discussionmentioning
confidence: 99%